The Application of Induced Pluripotent Stem Cells in Pathogenesis Study and Gene Therapy for Vascular Disorders: Current Progress and Future Challenges - Guang-Yin Peng; Yang Lin; Jing-Jing Li; Ying Wang; Hao-Yue Huang; Zhen-Ya Shen (Hindawi Limited, 2019)
Vascular disorders are complex diseases with high morbidity and mortality. Among them, the dilated macrovascular diseases (MVD), such as aortic aneurysm and aortic dissection, have presented a huge threat to human health. The pathogenesis of vascular diseases is mostly associated with property alteration of vascular endothelial cells (VECs) and vascular smooth muscle cells (VSMCs). Studies have confirmed that induced pluripotent stem cells (iPSCs) can be proliferated and differentiated into other somatic cells, such as VECs and VSMCs. And patient-specific cells could provide detailed human-associated information in regard to pathogenesis or drug responses. In addition, differentiated ECs from iPSC have been widely used in disease modeling as a cell therapy. In this review, we mainly discussed the application of hiPSCs in investigating the pathological mechanism of different inherited vascular diseases and provide a comprehensive understanding of hiPSCs in the field of clinical diagnosis and gene therapy.